Key Factors That Influence The Use Of Knowledge-Based Decision Support Systems In Medium-Sized Companies In Sudan - Mohamed Elshaiekh, Nour Eldin (2010)
The basic objectives of this dissertation are to identify the important factors influencing the use of K-BDSS tools in medium sized companies in Sudan and to understand how the organizational performance are affected by the use of K-BDSS.